Antineutrophil cytoplasmic antibody associated vasculitis: a converging diagnosis from neuropathy and testicular infarcts. Issue 11 (26th November 2022) - Mercer, Ross; White, Angus; Bates, Christopher
Abstract: Antineutrophil cytoplasmic antibody (ANCA) associated vasculitis encompasses a group of rare multi-system affecting diseases that can present with unremitting cases of common conditions. We present a case of a middle-aged gentleman admitted under Urology with epidymo-orchitits on multiple occasions. Ultrasound revealed segmental testicular infarcts, and he was managed conservatively. He re-presented shortly after discharge to the medical assessment unit with ulnar nerve paraesthesia, thought to be due to ulnar nerve entrapment syndrome. Less than 1 week later he was re-admitted again, with severe peripheral nerve pain in all limbs and multifocal weakness. Initial history and examination gave a provisional diagnosis of mononeuritis multiplex. Following investigations and treatment, this was deemed to be caused by a converging diagnosis of C-ANCA PR3 positive vasculitis, a small vessel vasculitis. This case highlights that patients with unremitting cases of epididymo-orchitis with testicular infarcts may benefit from autoimmune screening.